Analysis of mechanical properties and optimization of laser beam welding parameters on dissimilar metal titanium (Ti6Al4V) and aluminium (A6061) by factorial and ANOVA techniques. (2021) - Chandran, Sudhin; Rajesh, R.; Dev Anand, M.
Abstract: The Laser Beam Welding (LBW) is done among the two different materials titanium (Ti6Al4V) and aluminium 6061. The welding is done toward twenty-seven samples to improve and approve the mechanical and metallurgical properties. This welding is completed through three sets of process parameters and three sets of values. The mechanical properties like hardness and tensile strength are estimated for the workpiece, and the ultimate value is said to 290 HV and 205 MPa, separately. The factorial structure of the examination quantifies the reaction of each conceivable blend of factors and factor levels. ANOVA technique is used to advance the procedure boundaries to achieve the ideal joint quality and nature of joints in the welded tests. Likewise, it is utilized to distinguish the utmost prevailing process parameter in this welding procedure. The three process parameters with three sets of values are welding power (1600–2000 W), welding speed (2–2.4 m/min), and offset (0.2–0.4 mm). It is evident from the SEM micrographs demonstrated that there is no fastening imperfection in the interface.